Mengenal Kurikulum Merdeka di Sekolah Dasar (International Forum of Researchers and Lecturers, 2025)
Independent Curriculum schools are characterized by a wide variety of content that will be used to its fullest to provide opportunities for learners to explore ideas and improve skills. Teachers are free to choose the learning resources used to match learning with learners' interests and needs. This research uses the library research method. This research aims to describe in more detail the Merdeka curriculum in elementary schools. The literature approach was used in this study. In this study, the researchers collected journal articles from Google Scholar using the keywords Merdeka curriculum. Researchers found 10 articles related to the keywords used. After the articles were selected, the researchers conducted an in-depth analysis of the articles and presented them in the Results and Discussion section. The results of this study include an analysis of the characteristics, advantages and disadvantages, and implementation of Merdeka curriculum in elementary schools. The Merdeka curriculum has the potential to improve education standards in Indonesia as a whole with the right strategy and adequate support.